2006
DOI: 10.1063/1.2404604
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature nitrogen incorporation method for enhanced electrical properties in hafnia based gate dielectrics

Abstract: A low temperature method (∼400°C) for nitrogen incorporation in hafnia based dielectrics has been developed for future gate dielectric applications. Hf metal films were deposited on Si substrates in ammonia ambient and were subsequently oxidized under ultraviolet illumination. Using this method, an interfacial layer comprising Hf–Si–O–N bonding was formed at the hafnia-Si interface, which led to a substantial enhancement in the overall dielectric properties of the film. An equivalent oxide thickness of 11.5Å a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…An increase in nitrogen incorporation with the increase in the nitridation temperature has been reported earlier. 5 The densification of film and IL can be attributed to the presence of a larger amount of nitrogen. The increase in thickness of IL is due to higher diffusivity of oxygen and nitrogen at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in nitrogen incorporation with the increase in the nitridation temperature has been reported earlier. 5 The densification of film and IL can be attributed to the presence of a larger amount of nitrogen. The increase in thickness of IL is due to higher diffusivity of oxygen and nitrogen at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have already revealed that engineering IL by nitrogen incorporation improved the electrical properties of metal-oxidesemiconductor ͑MOS͒ device. 5 However, all the above mentioned results were qualitative studies. There are only a few quantitative reports for interface properties especially interface roughness change with respect to the nitridation process.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…27 However, additional IL degradation ͑IL growth and high interface state; D it ͒ may not be avoidable in case of high temperature nitridation method. 5,27 In conclusion, the UV assisted low temperature nitrogen doping technique for hafnia gate dielectric film was investigated. The incorporation efficiency of UV assisted low temperature method was comparable to the high temperature ͑ϳ650°C͒ thermal nitridation process.…”
mentioning
confidence: 99%
“…͓DOI: 10.1063/1.2892040͔ Hafnium silicate has been extensively studied as an alternative gate dielectric material in advanced metal oxide field effect transistors due to high crystallization temperature, thermodynamic stability with Si, high permittivity, and relatively large band gap ͑5.68 eV͒. [1][2][3][4][5][6][7] However, hafnium silicate film still has issues such as hafnium inter diffusion, lowk interface layer ͑IL͒ formation, and phase separation between hafnium and silicon oxides. Nitrogen incorporation in hafnium silicate was explored to enhance the resistance to thermal degradation.…”
mentioning
confidence: 99%